2008
DOI: 10.1183/09031936.00147507
|View full text |Cite
|
Sign up to set email alerts
|

Novel tests for diagnosing tuberculous pleural effusion: what works and what does not?

Abstract: Tuberculous pleuritis is a common manifestation of extrapulmonary tuberculosis and is the most common cause of pleural effusion in many countries. Conventional diagnostic tests, such as microscopic examination of the pleural fluid, biochemical tests, culture of pleural fluid, sputum or pleural tissue, and histopathological examination of pleural tissue, have known limitations. Due to these limitations, newer and more rapid diagnostic tests have been evaluated. In this review, the authors provide an overview of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 66 publications
3
121
0
13
Order By: Relevance
“…77 Wilkinson et al 73 found a 15-fold greater concentration of ESAT-6-specific spot-forming T cells in pleural fluid than of PBMCs in 10 patients with pleural TB. These cells were not found in the pleural fluid of 8 patients with nontuberculous pleuritis.…”
Section: Pleural Tuberculosismentioning
confidence: 99%
“…77 Wilkinson et al 73 found a 15-fold greater concentration of ESAT-6-specific spot-forming T cells in pleural fluid than of PBMCs in 10 patients with pleural TB. These cells were not found in the pleural fluid of 8 patients with nontuberculous pleuritis.…”
Section: Pleural Tuberculosismentioning
confidence: 99%
“…Approximately 30% of tuberculosis cases present as tuberculous pleurisy (Aktogu et al, 1996), for which the available diagnostic methods have significant limitations. Culture of pleural fluid shows sensitivities of only 24 to 58% (Trajman et al, 2008;Porcel, 2009), while pleural tissue biopsy is invasive and technically difficult (Pérez-Rodriguez and Jiménez Castro, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Even in cases where ADA is unavailable, the use of clinical and demographic information in combination with a cell differential count, in high incidence settings, can yield a diagnosis of TB with a high predictive value (25). This concept has been further advanced with a number of groups recommending the use of pleural fluid and clinical parameter combinations in the diagnosis of tuberculous pleural effusions which we described in this review.…”
Section: Resultsmentioning
confidence: 99%